PENGARUH AUDIT DELAY, REPUTASI AUDITOR, PERGANTIAN MANAJEMEN, FINANCIAL DISTRESS, PERTUMBUHAN PERUSAHAAN DAN KEPEMILIKAN PUBLIK TERHADAP AUDITOR SWITCHING PADA PERUSAHAAN MANUFAKTUR GO PUBLIC YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) 2010-2015 - Nurul Hidayati, Wahyu (Sekolah Menengah Kejuruan (SMK) Pustek, 2018)
This study aims to find out, analyze, prove and test the influence of Audit Delay, Auditor Reputation, Company Growth, Financial Distress, Change of Management and Public Ownership of Switching Auditors in Manufacturing companies listed on the Stock Exchange in 2010-2015. The sampling method used was purposive sampling; the population of manufacturing companies on the Stock Exchange was selected based on certain criteria. The data of this study were tested using the classical assumption test using multiple linear regression analysis techniques using SPSS version 24 for windows. The results showed that partially Audit Delay had no significant effect on the Switching Auditor, Auditor Reputation had no effect on the Switching Auditor, Management Change had an effect on the Switching Auditor, Financial Distress had no effect on the Switching Auditor, company growth had an effect on the Switching Auditor, Public Ownership had no effect on Switching Auditor, and simultaneously audit delay, Auditor Reputation, Management Change, Financial Distress, company growth, public ownership, have a significant effect on the Auditor Switching. The test is based on a confidence level of 89.4% and an error rate of 10.6%